Performance and properties of structural concrete made with corex slag - Jaufeerally, Hassen (Department of Civil Engineering, 2016)
Slag has been used in concrete as a cementitious extender for about 50 years in South Africa. Traditionally, blastfurnace slag has been used in concrete but recently a new product called Ground Granulated Corex Slag (GGCS) has become available on the market in the Western Cape Province. The objective of this research is to characterise the properties of this new product in concrete. In this study, the properties of corex slag concrete were compared to normal blastfurnace slag and plain CEM I concretes. A series of mixes was undertaken, with water:binder ratios varying between 0.4 and 0.3, and slag replacement levels between 30 and 70%. The physical characterisation of corex slag revealed that the material is finer than blastfurnace slag, having more ultra-fine particles. The oxide analysis showed that the higher proportions of the calcium and magnesium oxides present in corex slag increase the potential for hydraulic activity of the binder compared with blastfurnace slag. The investigation of the fresh concrete properties revealed that the consistence of concrete increases with the use of slag, especially at higher water:binder ratios. Blastfurnace slag performed marginally better than corex slag. The use of slag generally increased the setting time of the paste, with pastes containing corex slag having a shorter final setting time than those containing blastfurnace slag. The setting time was also found to increase with increasing stag replacement level. The increase in setting time caused the bleed time of slag concrete to increase but the total bleed volume was significantly reduced. The bleed properties of concrete were improved when corex slag was used. It was found that the compressive strength of the new cementitious material lagged behind that of CEM I controls during early ages but after seven days, corex slag concrete showed higher strength. The strength was observed to decrease with increasing water:binder ratio. From the compressive strength results, it was deduced that the optimum corex slag substitution rate varied with water:binder ratio, ranging from 45 to 60 % The elastic modulus of corex slag concrete was found to be equal to or higher than CEM I concrete, especially at low water:binder ratios (wtb = 0.4). Deformation experiments showed that corex slag concrete had the lowest creep and shrinkage strains of all the concretes at low water:binder ratios. At higher water:binder ratios, however, the shrinkage strains were in the same range as the other two materials. Prediction models were also assessed and it was found that no model was able to accurately predict both creep and shrinkage. Generally, the shrinkage predictions were more accurate. Durability index tests showed that corex slag concrete has good to excellent potential durability, based on historical data. Marine exposure testing indicated that corex slag binds a substantial amount of chlorides, hence reducing the risk of corrosion in marine environments. Furthermore, the risk of carbonation-induced corrosion is also decreased. Expansion associated with alkali-silica reaction is minimised with the use of corex slag and the efficiency of the material increases with replacement level. It is concluded that corex slag is an excellent extender for use in concrete. Finally, recommendations are made on the need to further characterise the properties of the material.